Modulation of Itch by Localized Skin Warming and Cooling - Kristen M. Sanders; Takashi Hashimoto; Kent Sakai; Tasuku Akiyama (Medical Journals Sweden, 2018)
Skin thermal changes modulate itch sensitivity. However, the mechanisms of this modulation are still unclear. Using mouse models of acute and chronic itch, we investigated whether local innocuous thermal stimulation of the skin alters itch sensitivity and if blockade of thermosensitive transient receptor potential (TRP) channels can reduce these changes. Localized thermal changes were achieved by placing a thermal probe in contact with the back skin for 30 s. Warming the skin significantly increased serotonin-evoked scratching and spontaneous scratching in the ovalbumin model of atopic dermatitis but decreased histamine-evoked scratching. These changes were blocked by a TRPV4 antagonist. Cooling the skin significantly increased serotonin-evoked scratching but reduced histamine-evoked scratching. The increase in serotonin-evoked scratching, but not the reduction of histamine-evoked scratching, was blocked by TRPM8 antagonism. Chloroquine-evoked scratching was unaffected by either warming or cooling. Our data indicate that different itch signaling pathways are differentially modulated by skin thermal changes.